Evaluasi Kesesuaian Lahan Tanaman Padi Sawah Irigasi (Oryza sativa L.) Di Desa Bakaran Batu Kecamatan Sei Bamban Kabupaten Serdang Bedagai - Koko Tampubolon Tampubolon; Razali Razali; Hardy Guchi (Universitas Sumatera Utara, 2015)
This study aimed to determine the level of the land suitability class of irigation rice (Oryza sativa L.) in Bakaran Batu village Sei Bamban sub district Serdang Bedagai regency. Conducted in Bakaran Batu village Sei Bamban sub district Serdang Bedagai regency and Geographic Information Systems Laboratory and Laboratory for Research and Technology Faculty of Agriculture, University of North Sumatra Medan in April to August 2014. Conducted using a survey that refers to the level of the limiting factors of land characteristics. Field observation data and the data matched the results of laboratory analysis (matching) with the criteria of rice land suitability classe. The results showed that there are 2 Unit Land Map (ULM) In Bakaran Batu village Sei Bamban sub district Serdang Bedagai regency. Extensive wetland area of 286.02 ha ULM 1 and area of 318.03 ha ULM 2. The actual land suitability classes for rice crops in the ULM 1 is marginally suitable / S3 rc, nr whereas potential land suitability class is marginally suitable / S3 rc. The limiting factor is the soil texture is permanent so it cannot be repaired. The actual land suitability classes for rice in the ULM 2 is the marginally suitable / S3 nr whereas potential land suitability class is moderately suitable / S2 nr. The limiting factor is the C-Organic and soil base saturation can be improved by liming, organic matter, straw composting and fertilizer containing K+, Ca2+, Mg2+, Na+ for example KCl, CaCO3, MgSO4.Keywords: land suitability evaluation, bakaran batu village, irigation rice